2021
DOI: 10.3389/fnmol.2021.704219
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Penicillin Exposure Affects Cortical Development and Sensory Processing

Abstract: The prevalent use of antibiotics in pregnant women and neonates raises concerns about long-term risks for children’s health, but their effects on the central nervous system is not well understood. We studied the effects of perinatal penicillin exposure (PPE) on brain structure and function in mice with a therapeutically relevant regimen. We used a battery of behavioral tests to evaluate anxiety, working memory, and sensory processing, and immunohistochemistry to quantify changes in parvalbumin-expressing inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…This study adds to a rapidly growing literature demonstrating that ABx treatment can lead to significant shifts in behavior in rodent models, whether exposure occurs in early life (e.g., Leclercq et al., 2017; Perna et al., 2021; Tochitani et al., 2016) or adulthood (e.g., Ceylani et al., 2018; Desbonnet et al., 2015; Gacias et al., 2016; Sylvia et al., 2017). We also demonstrated, for the first time, that maternal ABx treatment can significantly impact thermoregulation in unexposed offspring.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This study adds to a rapidly growing literature demonstrating that ABx treatment can lead to significant shifts in behavior in rodent models, whether exposure occurs in early life (e.g., Leclercq et al., 2017; Perna et al., 2021; Tochitani et al., 2016) or adulthood (e.g., Ceylani et al., 2018; Desbonnet et al., 2015; Gacias et al., 2016; Sylvia et al., 2017). We also demonstrated, for the first time, that maternal ABx treatment can significantly impact thermoregulation in unexposed offspring.…”
Section: Discussionmentioning
confidence: 82%
“…Several additional studies have reported changes in patterns of gene expression in brain (Champagne-Jorgensen et al, 2020;Kayyal et al, 2020;Volkova et al, 2021), changes in microglia and other aspects of neural development (Perna et al, 2021), and/or sex-dependent alterations in behavior (e.g., anxiety, sensorimotor gating, sociability; Champagne-Jorgensen et al, 2020;Kayyal et al, 2020;Perna et al, 2021) in offspring following exposure of dams to ABx.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysbiosis in mice can be obtained by exposing young animals to a cocktail of a broad spectrum of antibiotics that cause gut inflammation, depressive-like symptoms, social behavior and cognitive deficits, along with changes in brain neuronal firing and microglial–glial activation [ 178 ]. A recent study shows that perinatal exposure to antibiotics affects cortical development with a long-lasting effect on brain functions in young mice [ 184 ]. Perinatal penicillin exposure significantly increased sensorimotor gating and decreased the ability to discriminate between textures in adolescent mice.…”
Section: Early Antibiotics Exposure and The Risk Of Asdmentioning
confidence: 99%
“…Perinatal penicillin exposure significantly increased sensorimotor gating and decreased the ability to discriminate between textures in adolescent mice. These behavioral alterations were accompanied by increased spontaneous neuronal activities and a delayed maturation of inhibitory neuronal circuits [ 184 ]. An excess use of antibiotics induced neurotoxic effects on mice brain [ 185 ].…”
Section: Early Antibiotics Exposure and The Risk Of Asdmentioning
confidence: 99%